Tim-3: An Activation Marker and Activation Limiter of Innate Immune Cells - Han, Gencheng; Chen, Guojiang; Shen, Beifen; Li, Yan (Frontiers in Immunology, 2013)
Tim-3 was initially identified on activated Th1, Th17, and Tc1 cells and induces T cell death or exhaustion after binding to its ligand, Gal-9. The observed relationship between dysregulated Tim-3 expression on T cells and the progression of many clinical diseases has identified this molecule as an important target for intervention in adaptive immunity. Recent data have shown that it also plays critical roles in regulating the activities of macrophages, monocytes, dendritic cells, mast cells, natural killer cells, and endothelial cells. Although the underlying mechanisms remain unclear, dysregulation of Tim-3 expression on these innate immune cells leads to an excessive or inhibited inflammatory response and subsequent autoimmune damage or viral or tumor evasion. In this review, we focus on the expression and function of Tim-3 on innate immune cells and discuss 1) how Tim-3 is expressed and regulated on different innate immune cells; 2) how it affects the activity of different innate immune cells; and 3) how dysregulated Tim-3 expression on innate immune cells affects adaptive immunity and disease progression. Tim-3 is involved in the optimal activation of innate immune cells through its varied expression. A better understanding of the physiopathological role of the Tim-3 pathway in innate immunity will shed new light on the pathogenesis of clinical diseases, such as autoimmune diseases, chronic viral infections, and cancer, and suggest new approaches to intervention.